1968
DOI: 10.1126/science.159.3822.1469
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Increases Hepatic Smooth Endoplasmic Reticulum and Drug-Metabolizing Enzymes

Abstract: Rats were fed ethanol for 2 weeks along with diets either adequate or deficient in protein and choline, the latter intake being similar to that of many alcoholics. Hepatic lipids, smooth endoplasmic reticulum, and the activities of drug-metabolizing enzymes (aniline hydroxylase and nitroreductase) were increased with the adequate diet but more so with the deficient one. These results may explain the increased tolerance by alcoholics of drugs such as sedatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

1968
1968
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(48 citation statements)
references
References 6 publications
3
43
0
2
Order By: Relevance
“…Electron microscopy of the rat livers confirmed proliferation of SER as an effect of ethanol as previously described by Rubin et al (1968). The livers of female rats which received 15% ethanol in their drinking water contained more fat droplets than the livers of male rats.…”
Section: Percentage Ethanolmentioning
confidence: 56%
“…Electron microscopy of the rat livers confirmed proliferation of SER as an effect of ethanol as previously described by Rubin et al (1968). The livers of female rats which received 15% ethanol in their drinking water contained more fat droplets than the livers of male rats.…”
Section: Percentage Ethanolmentioning
confidence: 56%
“…The presence of bizarre shapes and giant mitochondria [61, 63] with an increased matrix density was also reported [56,66,72,97]. The changes involving the endoplasmic reticulum [109] consist of a marked proliferation of the smooth membranes with abundant vesicular structures. The alterations of the endoplasmic reticulum are, according to [56], the first morphological changes detectable in the liver cell after ethanol feeding to rats; they were observed, in fact, after few days of alcohol administration, while mitochondrial changes appeared some days later.…”
Section: Acetaldehyde Metabolismmentioning
confidence: 87%
“…However, the group of Lieber [117] and others [87] showed that (a) MEOS is active even in acatalasemic animals; (b) a reconstituted system consisting of the essential terms of drug metabolism, i.e., cytochrome P 450 , NADPH-cytochrome c reductase and synthetic phospholipids, is able to oxidize, besides benzphetamine (characteristic substrate of drug metabolism), ethanol and other alcohols too and that MEOS is adaptively increased after chronic ethanol consumption, like other drug metabolizing activities. The induction of drug metabolizing enzymes due to alcohol [56,73,108,109] and the fact that ethanol in vitro inhibits in a competitive way the same enzymes, could explain, at least in part, the increased tolerance of alcoholics to sedatives when sober and the enhanced sensitivity to sedatives when inebriated. The quantitative contribution of microsomal ethanol oxidation to the overall ethanol metabolism is another much (see in the following paragraphs), has a much higher K m for ethanol (8-10 mmol/l) compared to that of alcohol dehydrogenase (0.2-2 mmol/l); however, chronic alcohol consumption increases the activity of CYP2E1 by several times [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic ethanol consumption by rats results in a proliferation of the hepatic smooth endoplasmic reticulum and an increase in NADPH-cytochrome P-450 reductase and spectrally observable cytochrome P-450 (1)(2)(3). The induction of P-450 by ethanol is associated with an increase in the metabolism and, in some instances, in the toxicity of many compounds, including N-nitrosodimethylamine (4)(5)(6), acetaminophen (7)(8)(9), aniline (10)(11)(12), ethanol (13), and carbon tetrachloride (14)(15)(16).…”
mentioning
confidence: 99%